Dakwartistik: Prototipe Digitalisasi Dakwah Berbasis Kearifan Lokal dalam Konteks Budaya Mandar - Nirwan Wahyudi AR; Aminuddin Aminuddin; Irnawati Irnawati (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2026)
This study aims to develop a prototype of Dakwartistik as an innovation in culture-based digital Islamic preaching. Dakwartistik is conceptualized as both a framework and an applied model that integrates Islamic preaching with artistic expressions rooted in local wisdom. Mandar culture was chosen as the experimental context for examining the intersection of preaching, culture, and technology. The study employed a Research and Development (R&D) approach using the Design–Production–Evaluation (PPE) framework. Data were collected through library research, participatory observation of Mandar traditions, document analysis, and interviews with 10 informants selected through purposive sampling involving academics and practitioners in the fields of preaching, culture, and digital media. The data were analyzed qualitatively through data condensation, data display, and conclusion verification, supported by source and method triangulation. The findings reveal that the Dakwartistik prototype was successfully developed as a cross-device web-based application with a simple and accessible interface. The platform features a gallery of Mandar traditions, narratives containing Islamic values, and interactive user spaces. These findings highlight the potential of Dakwartistik as an adaptive culture-based digital preaching model that can be replicated in other cultural contexts.